HUBUNGANPENGETAHUAN IBU TENTANG NUTRISI DENGAN PERTUMBUHAN DAN PERKEMBANGAN BALITA (Di Posyandu Mawar Dusun Kempleng Kecamatan Purwoasri Kabupaten Kediri Tahun 2009) - Martiningsih, Martiningsih; Linawati, Wening Desy (Jurnal AKP, 2010)
Important period in growth and development is under five period food or nutrition have important actor ingrowth and development of under five, that nutrition of under five is different with adult people. To fulfillnutrition of under five needs education is status or motherâs knowledge that becomesone of factor of growthand development under five. If the nutrition of underfive is not or less completed, process of growth anddevelopment can be impeded. It becomes the background of this research by the title the connection betweenmotherâs know;edge about nutrition and development of under five. (in Posyandu Mawar KemplenghamletPurwoasri subdistric Kediri region). This research intends to know the connection between motherâsknowledge about nutrition and growth and development of inder five. This research design uses analyticcorrelation. Motherâs knowledge about nutrition of underfive becomes free variable. Growth anddevelopment of underfive become suspended sub variable. Population in this research were57 mothers withunderfive in Posyandu Mawar Kempleng orchard. The sampling technique is simple random sampling. It isgot from Gamma correlation for growth of underfive, p value = 0,00 underï¡= 0,05 or p value = 0,000 <ï¡= 0,05 and for development of underfive. P value = 0,001<ï¡= 0,05 it means that H2 received. So thereis connection between motherâs knowledge about nutrition and and growth development of under five. InPosyandu Mawar Kemplenghamlet.Motherâs knowledge about nutrition of underfive can influence growth and development of underfive so thatgrowth and development arenât suspended